In vitro characterisation of [177Lu]Lu-DOTA-C595 as a novel radioimmunotherapy for MUC1-CE positive pancreatic cancer - Ashleigh Hull; William Hsieh; William Tieu; Dylan Bartholomeusz; Yanrui Li; Eva Bezak (EJNMMI Radiopharmacy and Chemistry, 2023)
Abstract Background Pancreatic ductal adenocarcinoma (PDAC) continues to be a malignancy with an unmet clinical demand. Development of radioimmunoconjugates which target cancer-specific receptors provides an opportunity for radioimmunotherapy of both metastatic and primary PDAC. In this study, we characterised the in vitro behaviour of a novel beta-emitting radioimmunoconjugate [177Lu]Lu-DOTA-C595 as a therapeutic agent against PDAC. [177Lu]Lu-DOTA-C595 is designed to target cancer-specific mucin 1 epitopes (MUC1-CE) overexpressed on most epithelial cancers, including PDAC. Results A series of in vitro experiments were performed on PDAC cell lines (PANC-1, CAPAN-1, BxPC-3 and AsPC-1) exhibiting strong to weak MUC1-CE expression. [177Lu]Lu-DOTA-C595 bound to all cell lines relative to their expression of MUC1-CE. [177Lu]Lu-DOTA-C595 was also rapidly internalised across all cell lines, with a maximum of 75.4% of activity internalised within the PANC-1 cell line at 48 h. The expression of γH2AX foci and clonogenic survival of PANC-1 and AsPC-1 cell lines after exposure to [177Lu]Lu-DOTA-C595 were used to quantify the in vitro cytotoxicity of [177Lu]Lu-DOTA-C595. At 1 h post treatment, the expression of γH2AX foci exceeded 97% in both cell lines. The expression of γH2AX foci continued to increase in PANC-1 cells at 24 h, although expression reduced in AsPC-1. Clonogenic assays showed a high level of cell kill induced by [177Lu]Lu-DOTA-C595. Conclusion [177Lu]Lu-DOTA-C595 has favourable in vitro characteristics to target and treat MUC1-CE positive PDAC. Further investigations to characterise the in vivo effects and potential value of [177Lu]Lu-DOTA-C595 in other MUC1-CE expressing malignancies such as lung, ovarian and colorectal adenocarcinoma are warranted.